ANALYSIS OF ABUNDANCE AND TYPES OF MICROPLASTICS IN SEDIMENTS ON KARAPYAK BEACH, SAYANG HEULANG BEACH, AND SINDANGKERTA BEACH, WEST JAVA - Rinukti Sabila Aji, Purify
The accumulation of plastic waste in the ocean, driven by single-use products, uncontrolled disposal, and poor management, leads to its degradation into microplastics, a major component of environmental contamination. This study was conducted to explore the availability of microplastic in the southern coastal areas of West Java, which are characterized by large waves directly facing the Indian Ocean. These unique oceanographic conditions could influence the distribution and characteristics of microplastics, while research about microplastics in this region remains limited. This study assessed the abundance, characteristics, and polymer types of microplastics in sediments from three beaches: Sindangkerta Beach, Karapyak Beach, and Sayang Heulang Beach. Samples were analyzed using Chemical Wet Peroxide Oxidation (CWPO) and density separation to enhance the extraction and characterization, followed by polymer identification using FTIR. The results revealed variation in microplastic abundance across beaches and depths, with Sayang Heulang Beach consistently exhibiting the highest levels. In September 2023, the microplastic abundance at Sayang Heulang Beach at a depth of 10–20 cm was 35 particles/200 g dry sediment, increasing to 51 particles/200 g dry sediment in January 2024. Seasonal analysis showed significantly higher microplastic abundance during the rainy season (January) compared to the dry season (September). Characterization showed that fiber-shaped and colored microplastics were dominant in all aspect. Polymer analysis revealed the dominance of Low-Density Polyethylene (LDPE) at 27%, followed by High-Density Polyethylene (HDPE), Polypropylene (PP), and others in smaller amounts. This study underscores the complexity of microplastic abundance and highlights the importance of assessing their distribution, characteristics, and polymer composition.